Early impact of PCV7/PCV13 sequential introduction to the national pediatric immunization plan, on adult invasive pneumococcal disease: A nationwide surveillance study. Issue 9 (25th February 2015) - Regev-Yochay, Gili; Paran, Yael; Bishara, Jihad; Oren, Ilana; Chowers, Michal; Tziba, Yevgenia; Istomin, Valery; Weinberger, Miriam; Miron, Dan; Temper, Violeta; Rahav, Galia; Dagan, Ron; et al.
Abstract Background PCV7 was introduced as a universal childhood vaccination in Israel on July 2009 and was gradually replaced by PCV13 from November 2010. We report data on adult invasive pneumococcal disease (IPD), two years post PCV13 implementation. Methods An ongoing nationwide active surveillance (all 27 laboratories performing blood/CSF cultures nationwide), initiated in 2009, providing all blood/CSF Streptococcus pneumoniae isolated from persons ≥18 years. Capture-recapture method assured reporting of >95% cases. All isolates were serotyped in one central laboratory. Medical history and outcomes were recorded in ∼90%. Results Of 1809 IPD episodes, S. pneumoniae was isolated from the blood in 95% and most cases had pneumonia. Predisposing comorbidities were present in >70%. During the four study years, overall IPD incidence decreased from 9.2 to 7.2/100, 000, incidence of pneumonia and particularly severe pneumonia cases decreased significantly from 6.6 to 4.7/100, 000, (p = 0.029). Vaccine type (VT7/VT13) serotypes decreased by 70%/57% within 4 years. This was accompanied by a 52% increase in non-VT13 strains. These changes were most apparent in winter. PCV impact was most pronounced in younger adults (39% decrease in overall IPD with only a non-significant increase in non-VT13 cases) while in those >65 years a non-significant decrease in overall IPD was observed with a 64% increase in non-VT13 cases. Non-VT13 serotypes that increased significantly were 12F, 15A 10A and 6 C. A continuous reduction in isolates with penicillin MIC > 0.06 μg/ml was observed (26% to 11%, p < 0.001). Conclusions Four years after PCV7 and 2.5 years after PCV13 universal implementation in children, incidence of adult IPD caused by VT7 and VT13 decreased in all ages, mainly in younger adults. Despite increase in non-VT13 IPD, overall IPD decreased. Additional follow-up is needed to determine the long-term impact of PCV13.